P. Francastel: Interaction of Art and Technology - Gaižutis, Algirdas (Problemos, 1979)
A critical analysis of aesthetical views by Pierre Francastel, a well-known French art sociologist and art critic, is presented. The author’s attention is focused on solving the problem of interaction of art and technology. A number of constructive points of the theory by Francastel are singled out, such as, the accent of polysemantic character of a work of art, the growth of intellectual basis in creative work, etc.